기본심리욕구와 주관적 웰빙 간의 관계에서 투지의 매개효과: 한국과 중국 청소년 비교 연구 - 정구철(Goo-Churl Jeong); 김영화(Ying-Hua Jin) (한국콘텐츠학회 논문지, 20(8), 2020)
This study aimed to analyze the mediating effect of grit in the relationship between basic psychological needs and subjective well-being among Korean and Chinese adolescents. The study subjects were a total of 300 Korean and Chinese adolescents. As a result of the study, first, the Korean adolescents showed a high level of autonomy in basic psychological needs, while Chinese adolescents showed a high level of competence. Second, there was a significant positive correlation between basic psychological needs and grit as well as subjective well-being. Third, we established that the direct effect of basic psychological needs on subjective well-being was more potent in Korean adolescents than Chinese adolescents. Fourth, the indirect effect of basic psychological needs on subjective well-being through grit was statistically significant. Fifth, the mediating effect of grit was found to be stronger among Chinese youth than Korean youth. Based on these findings, we discussed the importance of grit to improve the subjective well-being of adolescents, and the approaches to improve Korean youth's competence and Chinese youth's autonomy. 본 연구는 한국과 중국 청소년들의 기본심리욕구와 주관적 웰빙 간의 관계에서 투지의 매개효과를 분석하기 위해 수행하였다. 연구대상자는 한국과 중국 청소년 각각 150명씩 총 300명이었다. 연구결과, 첫째, 한국 청소년들은 기본심리욕구의 자율성이 유의하게 높았고, 중국 청소년들은 유능성이 유의하게 높게 나타났다. 둘째, 기본심리욕구와 투지 및 주관적 웰빙 간에 유의한 정적 상관관계가 있었다. 셋째, 기본심리욕구가 주관적 웰빙에 미치는 직접효과는 한국 청소년들이 중국 청소년들보다 더 강한 것으로 나타났다. 넷째, 기본심리욕구가 투지를 통해 주관적 웰빙에 미치는 간접효과는 통계적으로 유의하게 나타났다. 다섯째, 투지의 매개효과는 중국 청소년들이 한국 청소년들보다 더 강한 것으로 나타났다. 이러한 연구결과를 중심으로 청소년들의 주관적 웰빙을 증진시키기 위한 투지의 중요성을 논의하고, 한국 청소년들의 유능성 증진과 중국 청소년들의 자율성 증진을 위한 접근 방향에 대해 논의하였다.